LEVEL OF GOLD IN FEMALE REPRODUCTIVE ORGANS OF FROG - SKANDHAN, K P; VALSA, J; GUSANI, P H; SUMANGALA, B; DINESH, K S (The Indian Journal of Animal Reproduction, 2023)
Total length of reproductive system (ovary, oviduct, uterus and cloaca) of fifteen female frogs (Rana tigrina)was analyzed to find out the level of element gold in it, at each level. Gold was present in all tissues; maximumwas in cloaca.
Keywords: Gold; Female Frog